ESTIMATING THE MEAN OF INVERSE GAUSSIAN DISTRIB WTION WITH KNOWN COEFFICIENT OF VARIATION UNDER ENTROPY LOSS (Journal of Sciences, Islamic Republic of Iran)
An estimation problem of the mean µ of an inverse Gaussian distribution IG(µ, C µ) with known coefficient of variation c is treated as a decision problem with entropy loss function. A class of Bayes estimators is constructed, and shown to include MRSE estimator as its closure. Two important members of this class can easily be computed using continued fractions